Influence of ecological restoration initiatives on emotional bonds between indigenous peoples and the Chinese alligator - Wu, Di; Gu, Jintu; Yu, Jiahao (Frontiers in Environmental Science, 2024)
As ecological restoration initiatives continue to revitalize degraded environments in the nature reserves, the dynamics of Indigenous people’s emotional relationships with wildlife undergo significant shifts. Drawing upon the theoretical framework of emotion sociology, this research explored the intricate social mechanisms shaping Indigenous emotions toward wildlife. This research used a questionnaire survey. Based on a 10% sampling proportion, this research used the Kish selection method to draw a random sample of 361 households from the Chinese Alligator Reserve. It found that the main effect of the family population outflow (Coeff = −32.62), traditional cultural loss (Coeff = −2.51), pop culture familiarity (Coeff = 1.60) on Indigenous-wildlife emotion was significant. Meanwhile, the moderating effect of income is also clearly significant. This reveals the mechanisms by which ecological restoration initiatives create Indigenous and wildlife emotional ties are social support, cultural shaping, and income stratification. These findings underscore the importance of considering social effects in conservation efforts to foster sustainable relationships between Indigenous communities and wildlife in the nature reserves.